Dental composite components induce DNA-damage and altered nuclear morphology in gingiva fibroblasts. Issue 11 (November 2015) - Styllou, Marianthi; Reichl, Franz-Xaver; Styllou, Panorea; Urcan, Ebru; Rothmund, Lena; Hickel, Reinhard; Högg, Christof; Scherthan, Harry
Abstract Objective Released dental composite components can damage human gingival fibroblasts (HGFs) and their DNA. The cytotoxicity, chromatin condensation and the induction of DNA double strand breaks (DSBs) by different compounds of dental composites was investigated using an improved γ-H2AX focus assay. Methods HGFs were incubated with the monomers: bisphenol-A-ethoxylate-dimethacrylate (Bis-DMA), bisphenol-A-glycerolate-dimethacrylate (BisGMA), ethyltriethylen glycol methacrylate (ETEGMA), glycidyl methacrylate (GMA), 1, 6-hexandiol-dimethycrylate (HDDMA), trimethylolpropane ethoxylate triacrylate (TMPTA), and acrylamide (ACR). DSBs were determined by enumerating γ-H2AX and 53BP1 foci colocalized at DSBs. Results A concentration-dependent induction of DSBs was found in the order: GMA > BisGMA > ACR > Bis-DMA > HDDMA > TMPTA > ETEGMA. HGFs exposure to GMA (0.3 mM) and to BisGMA (0.09 mM) induced the highest rate of DSB foci, i.e. 12-fold and 8-fold, respectively, relative to control (0.33 DSB foci/cell). At the highest concentrations (EC50) prominent changes in the chromatin morphology of HGF cell nuclei, i.e. compaction of nuclear chromatin and reduction of the area covered by the ovoid fibroblast nuclei, were observed. Nuclear condensation was significantly induced by GMA (1.7-fold at 0.3 mM) and BisGMA (1.6-fold at 0.09 mM), which correlated with the highest numbers of induced DSB foci (GMA, BisGMA, 3.9 and 2.6 foci/cell, respectively). Significance The improved γ-H2AX/53BP1 focus assay revealed a concentration-dependent increase in DSBs for all tested substances. Furthermore, concentration-dependent changes in HGF cell nucleus morphology was noted, demonstrating genotoxic effects of the substances tested.